Risk and ambiguity in 10-Ks: An examination of cash holding and derivatives use - Friberg, Richard; Seiler, Thomas (Journal of Corporate Finance, 2017)
We explore the role of ambiguity, as opposed to risk, in explaining firms' corporate financial policies. We create text based measures of ambiguity and risk for U.S. firms between 1995 and 2013. Measured ambiguity is high in for instance high tech industries, whereas the risk measure is high for homogeneous goods. Using within-firm variation to identify effects we find that greater ambiguity is associated with greater cash holdings and more risk with a higher probability of derivatives use. The results are in line with a simple model of liquidity management with ambiguity averse agents.